DEVELOPMENT OF HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE SIMULTANEOUS ANALYSIS OF AMLODIPINE AND VALSARTAN IN COMBINED DOSAGE FORM AND IN VITRO DISSOLUTION STUDIED - Yuryeva, Olga; Kondratova, Yuliya; Logoyda, Liliya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: A simple, rapid, and reproducible high-performance liquid chromatography method was developed for the simultaneous determination of amlodipine and valsartan in their combined dosage forms and for drug dissolution studies. Methods: A C18 column (Zorbax Eclipse Ð¥DB-C18, 5 Î¼m, 2.1 mm Ã— 150 mm) and a mobile phase of water:acetonitrile:trifluoroacetic acid (55:45:0.1 v/v/v) mixture were used for separation and quantification. Analyses were run at a flow rate of 0.4 mL/min and at ambient temperature. The injection volume was 5 Î¼L and the ultraviolet detector was set at 265 nm. The method was validated as per ICH guidelines. Results: Under these conditions, amlodipine and valsartan were eluted at 1.64 min and 4.08 min, respectively. Total run time was shorter than 7 min. The results were 99.6 Â± 0.6 and 98.5 Â± 0.8 for amlodipine and valsartan, respectively. Valsartan was released within 15 min (98.32%) and amlodipine was also released within 30 min (96.16%) both at a pH of 6.8. Conclusion: The developed method was applied successfully for quality control assay of amlodipine and valsartan in their combination drug product and in vitro dissolution studies.